Elliptic genera of two-dimensional N = 2 gauge theories with rank-one gauge groups - Benini, Francesco; Eager, Richard (Letters in mathematical physics, 2014)
We compute the elliptic genera of two-dimensional N = (2, 2) and N = (0, 2) -gauged linear sigma models via supersymmetric localization, for rank-one gauge groups. The elliptic genus is expressed as a sum over residues of a meromorphic function whose argument is the holonomy of the gauge field along both the spatial and the temporal directions of the torus.